Developing Model for Integrating Quranic Verses with Acquired Knowledge: An Inquiry-Based Learning Approach - Ahmad Bazli Ahmad Hilmi; Muhammad Hafiz Saleh; Selamat Amir; Adibah Sulaiman @ Mohamad (Brill, 2026)
Tier 2- Indexed by SCOPUS